MVDR beamforming for correlated signal with vector smoothing - Zhi-yong LIN; Jian-wu TAO (Tongxin xuebao)
The MVDR beamforming algorithm for correlated signal with smoothing was proposed based on electromagnetic vector sensor array.First,the decorrelation principle of MVDR beamforming with vector smoothing was analyzed,and the output SINR of VS-MVDR beamforming in the presence of a single correlated interference was derived.The proposed algorithm is suitable for arbitrary array structures and has better performance in multipath propagation.Simulation results are shown to verify the efficacy of the proposed algorithm.